Experimental model of bladder instability in rabbits - Balasteghin, Karina Tuma [UNESP] (2003)
OBJECTIVE: Propose a new experimental model of bladder instability in rabbits after partial bladder obstruction. MATERIALS and METHODS: Thirty North Folk male rabbits, weighting 1,700 to 2,820 g (mean: 2,162 g) were studied. The animals were distributed in 2 experimental groups, formed by 15 rabbits each: Group 1 - clinical control. In this group there was no surgical intervention; Group 2 - bladder outlet obstruction. In this group, after anesthetizing the animal, urethral cannulation with Foley catheter 10F was performed and then an adjustable plastic bracelet was passed around the bladder neck. It was then adjusted in order to not constrict the urethra. The following parameters were studied in M1 - pre-operative period; M2 - 4 weeks post-operatively moments: 1)- urine culture; 2)- cystometric study; 3)- serum creatinine and BUN. RESULTS: Bladder weight was 2.5 times larger in the group with obstruction than in the control group. Cystometric evaluation showed a significant increase in maximal vesical volume in the final moment at Group G2. However, there was no statistically significant difference among the groups studied. There was no statistically significant difference between maximal detrusor pressure and vesical compliance in the different moments or in the studied groups. There was an absence of uninhibited detrusor contractions in all the animals in group 1, and involuntary contractions were detected in 93% of group 2 animals. There was no significant variation in BUN and serum creatinine either among the groups or in the same group. CONCLUSIONS: We observed in the group with obstruction a bladder weight 2.5 higher than normal bladders. We detected involuntary contractions in 93% of the animals in group 2, establishing this experimental model as appropriate to secondary bladder instability and partial bladder outlet obstruction.